Exploring the future of edtech and the COVID-19 impact on digital learning in Bangladesh: A predictive analysis using EDA and regression analysis - Faria, Anika Tabassum; Das, Lipon Chandra; Bhattacharjee, Hridika; Tamim, Md. Abu Azad (American Journal of Education and Learning, 2024)
Digital learning has become an important component of the educational landscape in Bangladesh, and this study examines how it has affected Bangladesh, with a particular emphasis on the changes brought about by the COVID-19 pandemic. As a result of the epidemic, the number of e-learning platforms has increased significantly. The long-term viability of these e-learning platforms for academic and personal growth has raised concerns. We conducted a survey among 243 high school, university, and graduate students to collect a series of relevant data, evaluate the changes COVID-19 brings to the education sector, and gather the opinions and interests of students in Bangladesh towards e-learning platforms. In order to conduct a study of the data, both regression analysis and exploratory data analysis (EDA) were utilized. The findings pointed to a number of significant variables that affect digital education, including learning experiences, skill development, and accessibility. The results shed light on possible obstacles and prospects for e-learning in Bangladesh and offer insights into its future. We provide a number of recommendations for the efficient and sustainable growth of digital learning platforms, emphasizing the need for improved digital skills, improved infrastructure, and ongoing support for both teachers and students.